O catira e a tradição em Quirinópolis: uma prática cultural (1920-2008) - Lima, Mirtes Ferreira de Freitas (2014)
This is a dissertation titled: The Catira and tradition in Quirinopolis: a cultural practice (1920-2008). The research aims to understand the continuities and transformations in the practices and cultural representations in the Stone Lisa region, municipality of Quirinopolis-Go. This is a work of cultural history whose object of study is cultural practices, specifically, the Catira still lacking in scientific study, and aims to realize Catira through its features, representations and symbols. The research is supported in the literature and empirical research through oral reports, giving support to the cultural traditions of Catira through orality.